Microstructural evolution of supra‐nanostructure Al2O3/ZrO2 eutectic powders by combustion synthesis‐spray cooling. Issue 12 (24th June 2019) - Yu, Wanjun; Zheng, Yongting; Yu, Yongdong; Su, Xiaoyue
Abstract: Eutectic powders with fine microstructure are difficult to synthesize by crushing eutectic bulk because of the damage of crystal structure and the introduction of milling media during preparation process. In this work, a novel combustion synthesis‐spray cooling (CSSC) method is developed to fabricate supra‐nanostructure Al2 O3 /ZrO2 eutectic powders. CSSC is a kind of self‐heating technique, which simplifies operations, reduces costs and supplies ultra‐high cooling rate. The phase composition and the microstructural evolution are investigated using experiment studies and ANSYS simulation. During the process, the t‐ZrO2 are stabilized at room temperature because of the solubility of Al2 O3 in ZrO2 . The ultra‐high cooling rate greatly refined eutectic structure. Although the eutectic structure coarsens with increases in particle size, the interphase spacing of all particles reaches supra nanoscale. The work provides a route for preparing supra‐nanostructure Al2 O3 /ZrO2 eutectic powders and for better understanding the microstructural evolution.